The effect of psychological capital on leadership practices in Colombian SMEs (2013)
Psychological capital is a new concept that has awakened a special interest, due to its effect on well-being and satisfaction in the workplace, factors that are related to organizational development. The purpose of this study was to describe the psychological capital of a group of Colombian SME directors and determine if this exercises an effect on their leadership practices. To measure the variables that make up psychological capital, the Life Orientation Test, Revised (LOT-R), the Scale of Generalized Self-Efficacy (Escala de Autoeficacia Generalizada-EAG), the State Hope Scale (SHS) and the Resilience Scale (RS) were applied. Leadership practices were evaluated using the Inventory of Leadership Practices (Inventario de Prácticas de Liderazgo-IPL). According to the results, participants evidenced a high level of psychological capital in which optimism obtained the highest score. Psychological capital, as a global construct, influenced leadership characteristics, but not in the same way for all the practices studied. On the individual level, excluding optimism, the other psychological capital variables influenced the leadership practices, also in a differential manner.